2019
DOI: 10.1111/jfs.12739
|View full text |Cite
|
Sign up to set email alerts
|

Bacterial contamination and prevalence of antimicrobial resistance phenotypes in raw fruits and vegetables sold in Delhi, India

Abstract: Fresh fruits and vegetables contaminated with microbial pathogens can cause outbreaks of food poisoning and other enteric diseases if consumed raw. The objective of the present study was to determine the bacterial contamination and antibiotic resistance in fresh produce sold in Delhi, India. One hundred fifty samples of fruits and vegetables generally consumed raw were collected from retail and wholesale vendors of Delhi-NCR, India. Microbial contamination was studied by culturing 25 g of each sample. Antimicr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
14
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 20 publications
(14 citation statements)
references
References 23 publications
0
14
0
Order By: Relevance
“…CTX resistant Klebsiella spp. were also detected on onion, cucumber, tomato, chili pepper and ginger in India [ 26 ]. In Italy, K. ozaenae resistant to AMP, cefoxitin (FOX), CTX were detected in ready to eat (RTE) salad samples [ 27 ].…”
Section: Resultsmentioning
confidence: 99%
“…CTX resistant Klebsiella spp. were also detected on onion, cucumber, tomato, chili pepper and ginger in India [ 26 ]. In Italy, K. ozaenae resistant to AMP, cefoxitin (FOX), CTX were detected in ready to eat (RTE) salad samples [ 27 ].…”
Section: Resultsmentioning
confidence: 99%
“…In addition, consumers deem vegetables more advantageous to health; thus, there has been a noted increase in the consumption of vegetables instead of foods produced from animals ( Brookie, Best & Conner, 2018 ). However, uncooked vegetables can have high levels of microbial contamination, which in turn could lead to a high rate of cross-contamination events ( E. coli and K. pneumoniae –vegetables–human) ( Boonyasiri et al, 2014 ; Kim et al, 2015 ; Mritunjay & Kumar, 2017 ; Saksena, Malik & Gaind, 2020 ). In fact, it has been reported that ESBL-producing bacteria could be present in fresh vegetables such as iceberg lettuce, spinach, and tomato ( Blaak et al, 2014 ; Richter et al, 2019 ).…”
Section: Introductionmentioning
confidence: 99%
“…For instance, Salmonella typhi has been detected in orange juice samples in Mexico and the United States [15,16], and Escherichia coli and Vibrio cholera have been commonly found in Bangladesh and Japan [17,18]. The microbial contamination of fruit juices sold by street vendors has been reported in urban India, including the crowded places of Delhi, Uttarakhand, Punjab, Kolkata, Kerala, Hyderabad and Haryana [3,19,20]. The numbers of pathogens in the fruit juices are often reported to be above the permissible standards.…”
Section: Introductionmentioning
confidence: 99%